GE_GERICHTE C/26350/2008 vom 15. Januar 2010 - GE Cour de justice (2010)
; INTERNATIONAL | Distinction entre litige international et litige interne. | CL.2 CL.7 LDIP 5 LDIP.112 LDIP.127 LForst.7 CO.38 CO.39 CO.169